NEW ELECTIONS AND OLD CONCERNS: FEMALE POLITICAL RIGHTS AS A CONSTANT FIGHT - Bertholdi, Juliana; Kozicki, Katya; Bonatto, Marina (Revista da Faculdade de Direito do Sul de Minas, 2021)
In this study it is argued that female participation in politics is a basic requirement for achieving a democracy of greater quality, as well as for protecting the political rights secured in the international human rights system. Thus, by interpreting democracy beyond its mere procedural dimension, this paper proposes an analysis of the crisis of political participation, which is exacerbated by the exclusion of entire sectors of the population from the full exercise of their political rights, allowing them simply to vote and nothing more. Therefore, given that women’s difficult access to elected positions has been confirmed by recent Brazilian Supreme Electoral Tribunal studies, it becomes evident that our affirmative actions’ system is insufficient to fight this reality. Finally, we will seek to discuss new participation mechanisms, especially those regarding new perspectives in Brazilian legislation.